Jewish fictional letters from Hellenistic Egypt: the Epistle of Aristeas and related literature - White, L. Michael; Keddie, Anthony ca. 20./21. Jh. (Writings from the Greco-Roman world, 2018)
Cover -- Contents -- Acknowledgements -- Preface -- Abbreviations -- The Social Reality of Fictional Letters -- The Epistle of Aristeas -- The Early Reception of the Epistle of Aristeas -- Related Epistolary Literature -- Appendix: The Ptolemaic Rulers of Egypt -- Bibliography -- Index Verborum Graecorum -- Index of Ancient Sources -- Index of Modern Scholars -- Index of Subjects